Los discursos de la sostenibilidad: análisis de tendencias conceptuales a partir de mediciones bibliométricas (2016)
This paper discuss the publications about sustainability, this topic has been used between 1970 and 2015. The discussion is based on papers that analyze the sustainability in different contexts and the pattern of this analysis was the roots for the argument. According to the analysis, the concept of sustainability was initially associated with the study and minimization of negative external factors, in first world countries, from economic development policies. During the 80´s the trend of the literature reveals that big amount of documents, use not only the concept of sustainability, but an emerging concept of sustainable development.